The Role of Hormones and Trophic Factors as Components of Preservation Solutions in Protection of Renal Function before Transplantation: A Review of the Literature - Aneta Ostróżka-Cieślik; Barbara Dolińska (Molecules, 2020)
Transplantation is currently a routine method for treating end-stage organ failure. In recent years, there has been some progress in the development of an optimal composition of organ preservation solutions, improving the vital functions of the organ and allowing to extend its storage period until implantation into the recipient. Optimizations are mostly based on commercial solutions, routinely used to store grafts intended for transplantation. The paper reviews hormones with a potential nephroprotective effect, which were used to modify the composition of renal perfusion and preservation solutions. Their effectiveness as ingredients of preservation solutions was analysed based on a literature review. Hormones and trophic factors are innovative preservation solution supplements. They have a pleiotropic effect and affect normal renal function. The expression of receptors for melatonin, prolactin, thyrotropin, corticotropin, prostaglandin E1 and trophic factors was confirmed in the kidneys, which suggests that they are a promising therapeutic target for renal IR (ischemia-reperfusion) injury. They can have anti-inflammatory, antioxidant and anti-apoptotic effects, limiting IR injury.